Profiled Deck Composite Slab Strength Verification - Mohammed, K.; Abd Karim, I.; Bulu, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
The purpose of this article is to present an overview on alternate profiled deck composite slab (PDCS) strength verification devoid of the expensive and complex laboratory procedures in establishing its longitudinal shear capacity. Despite the several deterministic research findings leading to the development of proposals and modifications on the complex shear characteristics of PDCS that defines its strength behaviour, the laboratory performance testing stands to be the only accurate means for the PDCS strength assessment. The issue is critical and warrants much further thoughts from different perspective other than the deterministic approach that are rather expensive and time consuming. Hence, the development of a rational-based numerical test load function from longitudinal shear capacity consideration is a necessity in augmenting the previous futile attempts for strength determination of PDCS devoid of the costlier and expensive laboratory procedure.